Dimension as a business strategy - Sara Terrón-Ibá\~nez; María Elena Gómez-Miranda; Lázaro Rodríguez-Ariza (European Journal of Family Business (EJFB), 2020)
This paper analyzes the possible differences in the economic-financial situation of family organizations based on the business dimension. Then, we focus our analysis on SMEs to analyse the influence of the dimension in their performance. For this, information belonging to a large sample composed of 21,149 family businesses and 5,737 non-family businesses in Spain corresponding to the period 2003-2015 is studied. The conclusions obtained show that, although the increase in the dimension of the family organizations is positively related to their performance, there are limits beyond which the value of certain economic-financial indicators can be negatively affected. This behavior is not observed in non-family businesses.
Keywords: G4; M1; 650; Family business; economic and ﬁ nancial indicators; size; SMEs; productivity; ROA